2006
DOI: 10.1128/mcb.26.7.2675-2687.2006
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-Like Growth Factor 1 Receptor Signaling Regulates Skin Development and Inhibits Skin Keratinocyte Differentiation

Abstract: The insulin-like growth factor 1 receptor (IGF-1R) is a multifunctional receptor that mediates signals for cell proliferation, differentiation, and survival. Genetic experiments showed that IGF-1R inactivation in skin results in a disrupted epidermis. However, because IGF-1R-null mice die at birth, it is difficult to study the effects of IGF-1R on skin. By using a combined approach of conditional gene ablation and a three-dimensional organotypic model, we demonstrate that IGF-1R-deficient skin cocultures show … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
92
1
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 111 publications
(97 citation statements)
references
References 45 publications
2
92
1
2
Order By: Relevance
“…This is in contrast to cells lacking the expression of the IR or the IGF-1R (Sadagurski et al, 2006), where the proliferation process was abnormally decreased. There are several possibilities for interpreting these findings.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…This is in contrast to cells lacking the expression of the IR or the IGF-1R (Sadagurski et al, 2006), where the proliferation process was abnormally decreased. There are several possibilities for interpreting these findings.…”
Section: Discussionmentioning
confidence: 62%
“…One possible explanation for this finding can be that the IRS-2 protein has no role in the differentiation process and development of skin keratinocytes. Though, previously we have shown that IGF-1R inactivation results in precocious differentiation of skin keratinocytes, and that IRS-2 overexpression prevented this abnormally facilitated differentiation, suggesting that IRS-2 has an inhibitory role in the differentiation process (Sadagurski et al, 2006). However, IRS-2 overexpression had no effects on the normal differentiation process, suggesting that the possible role of IRS-2 in the differentiation process is not direct.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…4,5 Although generally recognized as a proliferation and survival factor for the skin, IGF-1 was recently also implicated in hair and skin morphogenesis. 6,7 In the skin, its levels must be strictly controlled because overexpression of IGF-1 in proliferating and in differentiating keratinocytes resulted in hyperplasia and tumor formation. 8,9 In addition to its role in skin homeostasis, several studies suggest a role of IGF-1 in skin repair.…”
mentioning
confidence: 99%
“…23) A three-dimensional culture containing keratinocytes derived from mouse embryonic stem cells grown on a matrix secreted from normal human fibroblasts also forms a thick epithelial sheet that resembles the epidermis of humans but not that of mice. 24) Recently, Sadagurski et al have demonstrated a mouse organotypic coculture using keratinocytes and fibroblasts, 25) which is similar to our coculture, but the keratinocyte sheet remains thicker. 25) The differences between our culture and theirs are the following: collagenase and trypsin for isolation of keratinocytes, FAD and Eagle's medium for cocultures.…”
Section: Discussionmentioning
confidence: 73%